Legal Harmonization of Electronic Evidence within Indonesia’s Criminal Justice System - Imroatun Solekah; Teddy Delano (Iustitia: Journal of Legal Theory, Politics, and International Relations, 2026)
This study examines the harmonization of electronic evidence regulation within Indonesia’s criminal justice system by analyzing normative inconsistencies between the Criminal Procedure Code, the Information and Electronic Transactions Law, and sectoral electronic system regulations. The research employs a normative doctrinal and comparative legal approach using statutory interpretation, conceptual analysis, and comparative legal reasoning to evaluate admissibility standards, authentication procedures, evidentiary value, and procedural safeguards governing electronic evidence. The findings demonstrate that fragmented evidentiary regulation has generated judicial inconsistency concerning digital authentication, forensic verification, chain of custody, and procedural legality in criminal proceedings. Indonesian courts continue to apply divergent interpretations regarding the relationship between electronic evidence and the principle of negative statutory proof, particularly in relation to evidentiary reliability and constitutional due process. The study proposes a harmonized evidentiary governance model integrating procedural codification, forensic standardization, institutional synchronization, and unified judicial interpretation in order to strengthen legal certainty, procedural fairness, and technological accountability within Indonesia’s digital criminal justice administration. The proposed framework reinforces institutional coherence across investigation, prosecution, and adjudication processes.